Microstructure evolution of Cr2AlC MAX phase under a graphite bed between 1100 °C and 1500 °C. Issue 3 (1st February 2023) - Cheng, Yaping; Chen, Junfeng; Zhang, Yu; Liu, Wenyuan; Nath, Mithun; Wei, Yaowu; Yan, Wen; Zhang, Shaowei; Li, Nan
Abstract: Thermal decomposition behaviors and microstructure evolution of porous Cr2 AlC pellet samples in a graphite bed (65% N2 and 35% CO) between 1100 °C and 1500 °C were investigated to explore its potential slag-contact application. A walnut-like structure made of a porous chromium carbides core and Al2 O3 shell was confirmed on the original Cr2 AlC particle because of the formation of Al-depleted Cr2 Al1-x C in the graphite bed atmosphere. After heat treatment at 1300 °C, depletion of Al within the Cr2 AlC particle caused to generate a ∼650 μm thickness CrCx-enriched layer on the sample's surface and a highest Vickers hardness of 13.7 GPa. When the temperature rose to 1500 °C, cracks occurred in the sample because of the volumetric expansion from further decomposition. The degradation mechanism of fine-Cr2 AlC particles in the range from 1100 °C to 1500 °C was proposed in detail. Highlights: The degradation process of the porous Cr2 AlC samples in a graphite bed between 1100 and 1500 °C was investigated. A walnut-like core-shell structure, made of porous chromium carbide and dense Al2 O3 was confirmed on the original Cr2 AlC particles. The porous Cr2 AlC samples processed a CrCx-enriched shell with a depth of ∼650 μm after being fired at 1300 °C and endowed it with a high Vickers hardness of 13.7 GPa.